2023
DOI: 10.1002/hsr2.1138
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, knowledge, and skills towards artificial intelligence among healthcare students: A systematic review

Abstract: Background and Aims: This systematic review examined healthcare students' attitudes, knowledge, and skill in Artificial Intelligence (AI).Methods: On August 3, 2022, studies were retrieved from the PubMed, Embase, Scopus, and Web of Science databases. Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations were followed. We included crosssectional studies that examined healthcare students' knowledge, attitudes, skills, and perceptions of AI in this review. Using the eligibility requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 73 publications
(481 reference statements)
8
36
0
1
Order By: Relevance
“…49,50 In this sense, several studies in other professional areas comment that students and graduates already use AIbased technologies to significantly improve and increase efficiency and effectiveness in the areas they intend to develop throughout their lives [51][52][53][54][55] . This research shows that artificial intelligence is transforming the way business is done, creating a competitive advantage for companies seeking to understand and effectively apply these tools and also the way they select new personnel; 56 this said, the impact of artificial intelligence on the employment of university students is extremely worrying for those who are not adapting to this global technology; if you are not in the digital world, you will disappear, and you will have fewer job opportunities 57 .…”
Section: Discussionmentioning
confidence: 99%
“…49,50 In this sense, several studies in other professional areas comment that students and graduates already use AIbased technologies to significantly improve and increase efficiency and effectiveness in the areas they intend to develop throughout their lives [51][52][53][54][55] . This research shows that artificial intelligence is transforming the way business is done, creating a competitive advantage for companies seeking to understand and effectively apply these tools and also the way they select new personnel; 56 this said, the impact of artificial intelligence on the employment of university students is extremely worrying for those who are not adapting to this global technology; if you are not in the digital world, you will disappear, and you will have fewer job opportunities 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the majority of the knowledgeable participants were men, and almost 77% of them were unaware of AI's use in medicine. These findings illustrate that despite having a basic understanding of AI, medical students may not be familiar with its practical applications [30].…”
Section: The Student's Knowledge Of the Meaning Of Artificial Intelli...mentioning
confidence: 96%
“…Among the 38 studies examined, 26 investigated the level of awareness of AI among healthcare students. Out of these, 18 studies indicated that the student's knowledge level was subpar, at 50% [30].…”
Section: The Student's Knowledge Of the Meaning Of Artificial Intelli...mentioning
confidence: 99%
“…This increasing exposure to AI has resulted in mixed attitudes. Pessimistic views highlight the potential of AI to automate and replace humans in various elds (5). Optimists in the medical eld suggest that physicians who embrace AI will have more opportunities to bene t from future developments (6) and more time to develop non-technical skills for patient care.…”
Section: Introductionmentioning
confidence: 99%